Improving Online Customer Satisfaction: A Study on Biba - Pérez-Restrepo, Camilo; López, Carolina Ardila; Singh, Padmalini; Ochoa, Ana Maria Restrepo; Ceballos, Daniela Villegas; Tilekar, Geeta Dilip; Kaakandikar, Rishikaysh; F, Mohamed Saifuddin (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2021)
This paper aims to study the online shopping experience of Biba, the Indian brand for women's ethnic apparel to propose pertinent changes to improve the satisfaction of their customers when buying online in the context of the current global pandemic. This study employed a survey as a primary source, and relevant academic literature as secondary sources. The findings revealed the amount of apparel bought online has increased during the pandemic in addition to some general difficulties when buying clothes online and a general feeling of dissatisfaction. Other findings suggest that it is pertinent for Biba to make various changes, like a website makeover, the creation of a mobile phone application, and the diversification of their models’ catalog.